2019
DOI: 10.1177/0271678x19864081
|View full text |Cite
|
Sign up to set email alerts
|

Validation and noninvasive kinetic modeling of [11C]UCB-J PET imaging in mice

Abstract: Synaptic pathology is associated with several brain disorders, thus positron emission tomography (PET) imaging of synaptic vesicle glycoprotein 2A (SV2A) using the radioligand [11C]UCB-J may provide a tool to measure synaptic alterations. Given the pivotal role of mouse models in understanding neuropsychiatric and neurodegenerative disorders, this study aims to validate and characterize [11C]UCB-J in mice. We performed a blocking study to verify the specificity of the radiotracer to SV2A, examined kinetic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 40 publications
4
87
0
Order By: Relevance
“…In our hands, in situ preparation of boronic acid worked sluggishly (Table and Table S1). Based on the method developed by Onega et al, hydrochloric acid was employed and reaction progress monitored by the liquid chromatography‐mass spectrometry (LCMS) using HCl in different solvents. The application of HCl in dioxane gave none of the desired boronic acid 4 (entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our hands, in situ preparation of boronic acid worked sluggishly (Table and Table S1). Based on the method developed by Onega et al, hydrochloric acid was employed and reaction progress monitored by the liquid chromatography‐mass spectrometry (LCMS) using HCl in different solvents. The application of HCl in dioxane gave none of the desired boronic acid 4 (entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…The radiosynthesis of [ 11 C]UCB-J is based on the application of the palladium(0)-mediated Suzuki cross-coupling reaction between the carbon-11 methyliodide ([ 11 C]CH 3 I) and trifluoroborate precursor 3 (Figure 1). 7,10,11,13,14 Initially explored method employed a more common Suzuki reacting partner, ie, the corresponding boronic acid 15 (eg, 4 in Scheme 1) as a radiolabelling precursor; however, the boronic acid precursor 4 proved to be unstable upon storage resulting in poor reproducibility and unreliable radiochemical yields. Further investigation indicated that while trifluoroborate 3 can be used as a radiolabelling precursor for [ 11 C]UCB-J, the actual reacting specie is the boronic acid, thus necessitating a need for a mixture of trifluoroborate 3 and 3-10% of the boronic acid 4 to be present in the reaction vessel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, we generated a population-based metabolite curve in order to adjust for the peripheral metabolism and to validate the applicability of a noninvasive IDIF over the metabolite-corrected plasma input function. A limitation in the use of a population-based correction is the need of high inter-individual reproducibility; otherwise, under-or overestimations in the quantification may be introduced since the same curve is applied to all the subjects as we recently reported for the radioligand [ 11 C]UCB-J [13]. Since correcting the noninvasive IDIF for metabolism did not improve the agreement to V T (AV shunt, Corr) , we will use the uncorrected IDIF as noninvasive input function.…”
Section: Discussionmentioning
confidence: 99%
“…In order to generate a population-based metabolite correction to account for peripheral radiometabolism, we measured parent fractions in a cohort of WT mice (n = 3 per time point) at 5, 15, and 30 min p.i. The procedure was done adapting the previously described methodology [13] to [ 11 C]ITDM. Details of the procedure are provided in the ESM.…”
Section: Metabolite Correctionmentioning
confidence: 99%